DESKRIPSI KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII PADA SOAL TIMSS DITINJAU DARI KEMAMPUAN AWAL - Nisrina Hani Prasetyo; Ramlah Ramlah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This research aims to determine the students’ math problem-solving ability according to the students’ initial ability category. The subjects of this study were randomly selected and obtained 3 students of class VIII in one of the junior high schools in Tambun Selatan, Bekasi. The method used is descriptive qualitative with interactive model data analysis from Miles & Huberman. The instrument used is the 2011 TIMSS question as a test of students' mathematical problem solving abilities in terms of initial abilities and semi-structured interviews to the 3 students. The indicator of mathematical problem solving ability used is the Polya indicator which consists of understanding the problem, device a plan, carry out the plan and looking back. The results showed that students with low initial abilities had not been able to pass the four indicators of problem solving abilities. Students with intermediate initial ability can pass two problem-solving ability indicators, while students with high initial ability can pass three problem-solving ability indicators